Drosophila melanogaster diabetes models and its usage in the research of anti-diabetes management with traditional Chinese medicines - Miao, Yaodong; Chen, Rui; Wang, Xiaolu; Zhang, Jie; Tang, Weina; Zhang, Zeyu; Liu, Yaoyuan; Xu, Qiang (Frontiers in Medicine, 2022)
The prevalence of diabetes mellitus (DM) is increasing rapidly worldwide, but the underlying molecular mechanisms of disease development have not been elucidated, and the current popular anti-diabetic approaches still have nonnegligible limitations. In the last decades, several different DM models were established on the classic model animal, fruit fly (Drosophila melanogaster), which provided a convenient way to study the mechanisms underlying diabetes and to discover and evaluate new anti-diabetic compounds. In this article, we introduce the Drosophila Diabetes model from three aspects, including signal pathways, established methods, and pharmacodynamic evaluations. As a highlight, the progress in the treatments and experimental studies of diabetes with Traditional Chinese Medicine (TCM) based on the Drosophila Diabetes model is reviewed. We believe that the values of TCMs is underrated in DM management, and the Drosophila Diabetes models can provide a much more efficient tool to explore the values of it.